Hilary Conroy y T.S. Miyakawa, ed., East Across the Pacific, Santa Bárbara, California, American Bibliographical Center-Clio Press, 1972, 322 pp. - Ota Mishima, María Elena (Estudios de Asia y África, 1976)
-